Novel GCH1 variant in Dopa-responsive dystonia and Parkinson's disease. Issue 4 (April 2015) - Lewthwaite, A.J.; Lambert, T.D.; Rolfe, E.B.; Olgiati, S.; Quadri, M.; Simons, E.J.; Morrison, K.E.; Bonifati, V.; Nicholl, D.J.
Abstract: Background: GTP cyclohydrolase I ( GCH1 ) mutations are the commonest cause of Dopa-responsive dystonia (DRD). Clinical phenotypes can be broad, even within a single family. Methods: We present clinical, genetic and functional imaging data on a British kindred in which affected subjects display phenotypes ranging from DRD to Parkinson's disease (PD). Twelve family members were studied. Clinical examination, dopamine transporter (DAT) imaging, and molecular genetic analysis of GCH1 and the commonest known familial PD-related genes were performed. Results: We have identified a novel missense variant, c.5A > G, p.(Glu2Gly), within the GCH1 gene in affected family members displaying a range of phenotypes. Two affected subjects carrying this variant had abnormal DAT imaging. These two with abnormal DAT imaging had a PD phenotype, while the remaining three subjects with the novel GCH1 variant had normal DAT imaging and a DRD phenotype. Conclusions: We propose that this GCH1 variant is pathogenic in this family and these findings suggest that similar mechanisms involving abnormal GTP cyclohydolase I may underlie both PD and DRD. GCH1 genetic testing should be considered in patients with PD and a family history of DRD. Highlights: We have identified a novel missense variant, c.5A > G, p.(Glu2Gly), within the GCH1 gene in family with Dopa responsive dystonia (DRD) and parkinsonism. Those with parkinsonism had abnormal DaTscans, indicating nigrostriatal neurodegeneration. These findings suggest that similar mechanisms involving abnormal GTP cyclohydolase I may underlie both Parkinson's disease and Dopa responsive dystonia.